Using a theoretical framework of Intervention Mapping to inform public health communication messages designed to increase vaccination uptake; the example of mpox in the Netherlands - Ymke J. Evers; Francine Schneider; Veja Widdershoven; Cornelia J. D. Goense; Charlotte M. M. Peters; Sjoerd G. van Elsen; Christian J. P. A. Hoebe; Nicole H. T. M. Dukers-Muijrers (BMC, 2023)
Abstract Introduction During an infectious disease outbreak, primary preventive pre-exposure vaccination (PPV) could substantially increase the potential for its control, if uptake is sufficiently high. An important tool to increase PPV uptake, are communication strategies, with tailored messages targeted to modify determinants for PPV uptake. Here, we take the example of the 2022 mpox multicountry outbreak, as we inform the development of communication strategies by applying a theoretical framework for selecting effective communication strategies. Methods The theoretical framework Intervention Mapping (IM) was applied during the outbreak to inform communications [program]. Steps included: 1. Creating a logic model of the problem [not accepting PPV] by reviewing available literature, conducting an online survey among people at risk of mpox exposure, and consulting community-members, healthcare-and communication professionals; 2. Creating a matrix of change [from lower to higher PPV acceptance]; and 3. Selecting theory-based methods and practical applications for communication messages to achieve the intended behaviour change (getting vaccinated). Results The program objective was to promote PPV uptake in people at risk of mpox exposure. Important changeable determinants identified included perceived risk and severity of mpox, importance to protect against mpox [attitude], experienced effectiveness of vaccination and side-effects [response efficacy], and social norm. Theory-based communication methods for optimizing these determinants include provision of facts [increasing knowledge], personalized risk and scenario-based risk information [addressing risk perception/severity], elaboration, arguments [stimulating a positive attitude], gain framing [increasing perceived response efficacy], guided practice [increasing skills/self-efficacy in overcoming barriers] and social norm approach [demonstrating positive norm]. Other key important factors include that communication delivery is uniform (across channels), clear, accessible, and with stigma-free messaging, and that is well-timed and repeated. Conclusion IM provided a valuable tool in selecting communication methods to promote mpox vaccination uptake. These methods can be used to (more quickly) produce and implement a communication program in the context of possible future, vaccine-preventable, infectious disease outbreaks.